A SOCIO-ONOMASTIC ANALYSIS OF THE SELECTED SCHOOL NAMES - Kennedy N. Kangwa, Pethias Siame, Ph.D, Reuben Chulu Chupa,; Djalilova Malika Shuxratovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This paper interrogates the societal circumstances that surround the names that were given to selected primary and secondary schools. The study, therefore, seeks to identify and reveal the culture and history embedded in these names by looking at the significance of the naming of twelve government schools in the Kabwe District of Central Province from a socio-onomastic point of view. The sample schools have full names of people, that is, first and surname. A qualitative case study design was chosen to guide the study. Semi-structured face-to-face interviews, followed by telephonic interviews and document analysis were used to collect data from twelve participants who represented the twelve sample schools. A phenomenological theoretical locale was adopted to underpin the study. The study shows that human beings have a deep-rooted need to name things influenced by particular phenomena and researchers have long recognized that there is much power in naming things. The study also reveals that names are given to human beings, things, and places to identify, symbolize, refer to, describe, simplify, and organize. The study also reveals that before the written alphabet was developed, and as far back as oral history existed, humans felt duty-bound to name things, people, and even weather patterns. The study further shows that the naming practice goes beyond cultures and religions, geographies, and periods, from primitive tribes to the present day. Therefore, the names are a historical record that carries some aspects of a people's way of life which include their history, beliefs, and customs among others.